Carvacrol Protects against Hepatic Steatosis in Mice Fed a High-Fat Diet by Enhancing SIRT1-AMPK Signaling. (20th February 2013) - Kim, Eunkyung; Choi, Youngshim; Jang, Jihee; Park, Taesun
Abstract : We investigated the protective effect of carvacrol against high-fat-diet-induced hepatic steatosis in mice and the potential underlying molecular mechanisms. Mice were fed a normal diet, high-fat diet, or carvacrol-supplemented high-fat diet for 10 weeks. Compared to mice fed the high-fat diet, those fed the carvacrol-supplemented diet showed significantly lower hepatic lipid levels and reduced plasma activities of alanine aminotransferase and aspartate aminotransferase and plasma concentrations of monocyte chemoattractant protein 1 and tumor necrosis factor α . Carvacrol decreased the expression of LXR α, SREBP1c, FAS, leptin, and CD36 genes and phosphorylation of S6 kinase 1 protein involved in lipogenesis, whereas it increased the expression of SIRT1 and CPT1 genes and phosphorylation of liver kinase B1, AMP-activated protein kinase, and acetyl-CoA carboxylase proteins involved in fatty acid oxidation in the liver of mice fed the high-fat diet. These results suggest that carvacrol prevents HFD-induced hepatic steatosis by activating SIRT1-AMPK signaling.